2014
DOI: 10.1177/0308575914532057
|View full text |Cite
|
Sign up to set email alerts
|

Changing lives and changing minds: the experiences of adoptive parents from application to approval

Abstract: The recruitment and preparation of adoptive parents is currently high on the UK Government's agenda and a number of far-reaching changes in policy, processes and guidance have been introduced in recent months. The fundamental aim of adoption from care remains to provide, hopefully, stable and loving families for children whose parents cannot care for them, but the experiences of adoptive parents in this process have recently moved from the wings to centre stage. This article introduces the reflections of a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 4 publications
2
16
0
9
Order By: Relevance
“…Freeman et al (2009) noted that most of the parents of children conceived via donor gametes who were motivated to consult the Donor Sibling Registry did so because of their desire to find donor siblings for their offspring. The importance of cross-generational sibling connections in the minds of the families we interviewed also coincides with the emphasis in UK social work on keeping groups of adopted siblings together or at least in touch with their genetic siblings (Dance and Farmer 2014).…”
Section: Discussionsupporting
confidence: 62%
“…Freeman et al (2009) noted that most of the parents of children conceived via donor gametes who were motivated to consult the Donor Sibling Registry did so because of their desire to find donor siblings for their offspring. The importance of cross-generational sibling connections in the minds of the families we interviewed also coincides with the emphasis in UK social work on keeping groups of adopted siblings together or at least in touch with their genetic siblings (Dance and Farmer 2014).…”
Section: Discussionsupporting
confidence: 62%
“…And what would the children be like? The emotional impact of unsafe uncertainty seemed to be heightened in the pre-adoption process when couples relayed 'horror stories' of profiling meetings, as Dance & Farmer (2014) also have indicated. This suggests that it is important for adoption practitioners to look further into how adopters can TRANSITION INTO ADOPTIVE PARENTHOOD be helped to achieve a sense of confidence in their capacity to parent prior to having children with significant needs placed with them.…”
Section: Discussionmentioning
confidence: 89%
“…Qualitative studies have begun to explore adoptive parents' experiences. For example, one prospective study of a U.K. sample of 27 adoptive parents highlighted the challenges parents encountered in adopting from their initial application to finally being selected, a process that on average took around two years to complete (Dance & Farmer, 2014). An earlier study of 39 Canadian couples who had adopted a child within the preceding two years likewise concluded that the transition to adoptive parenthood was stressful (Daniluk and Hurtig-Mitchell, 2003).…”
Section: Transition Into Adoptive Parenthoodmentioning
confidence: 99%
“…Previous research has explored the notion of “stretching”, which is where approved adopters expand their initial preferences in order to consider children from a wider age range or with more complex needs than they had initially hoped for (Dance & Farmer, ). This stretching was identified in the analysed online posts, where there were clear references made by adopters, albeit often quite reluctantly, to extending preferences in order to increase the chances of being matched with a child.…”
Section: Analysis Of Online Postsmentioning
confidence: 99%